Mental Health of Violence Survivors: Analysis of Resilience Levels with Emotion Regulation as a Moderator - Pusvitasari, Putri; Mumpuni, Niken Wahyuning Retno; Arifani, Hasnatya Adya (MOTIVA: JURNAL PSIKOLOGI, 2025)
Abstract :The acts of violence that are currently occurring are attracting enough public attention, be it physical, psychological, sexual, or domestic violence. Violence that occurs can have an impact on psychological disorders, thus affecting a person's mental health. To face this condition, survivors of violence need resilience, which is expected to help them survive so they can continue to live their daily lives well. The problems experienced by survivors of violence also involve emotions; where when individuals are able to regulate their emotions well, they will be able to achieve better mental health. This research aims to examine the moderating effect of emotional regulation on the relationship between resilience and mental health in survivors of violence. The research was conducted by distributing the scale to 101 female and male survivors of gender violence in Yogyakarta. Resilience was measured using the resilience scale, mental health was measured using the mental health scale (SKM-12), and emotional regulation used the emotion regulation scale. Data was processed using moderated regression analysis using the absolute difference test method. The results show that resilience (p = 0.000) directly influences mental health. Meanwhile, emotional regulation (p = 0.208) does not influence mental health. However, emotional regulation has been proven to moderate the relationship between resilience and mental health in survivors of violence.